Analisis Pengaruh Self-reward Lifestyle, Perilaku Shopaholic, dan Fear Of Missing Out (FOMO) terhadap Pola Belanja Konsumtif dan Pengelolaan Keuangan Generasi Z - Widiya Indah Lestari; Nur Ahmadi Bi Rahmani; Ahmad Perdana Indra (Jurnal Riset Akuntansi, 2026)
The development of digital technology and social media has driven changes in Generation Z's consumption behavior, particularly through self-reward lifestyle, shopaholic behavior, and Fear of Missing Out (FOMO). These three factors have the potential to increase consumptive spending patterns and decrease the quality of financial management. This study aims to analyze the influence of self-reward lifestyle, shopaholic behavior, and FOMO on consumptive spending patterns and financial management of Generation Z. This study uses a quantitative method with a causality approach. The research sample consisted of 152 Generation Z students majoring in Islamic Banking at UIN North Sumatra who were selected using the Slovin formula. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with the help of IBM SPSS 26. The results showed that self-reward lifestyle, shopaholic behavior, and FOMO have a positive and significant effect on consumptive spending patterns. In addition, the third variable also has a negative and significant effect on Generation Z's financial management. These findings emphasize the importance of controlling consumptive behavior and increasing financial literacy to create more rational and sustainable financial management.